The Use of Enhanced External Counterpulsation in the Treatment of Patients with Coronary Artery Disease - K. S. Karaganov; A. S. Lishuta; Y. N. Belenkov (Столичная издательская компания, 2020)
Enhanced external counterpulsation (EECP) is one of the most effective and safe non-invasive methods of treatment for patients with coronary artery disease (CAD), including complicated chronic heart failure (CHF). This method of therapeutic neoangiogenesis, used in conjunction with traditional drug therapy and myocardial revascularization, can significantly improve the quality of management of these patients.Aim. To study the effect of the EECP course on exercise tolerance, quality of life, structural and functional parameters of blood vessels in patients with verified stable CAD complicated by CHF.Material and methods. Patients (n=70) with verified stable CAD (angina pectoris class II-III) complicated by CHF class II-III (NYHA) were included in non-randomized uncontrolled study. Data from 67 patients (48 to 74 years old; 47 men and 20 women) were included in the final analysis. All patients had a course of EECP (35 one-hour procedures with a compression pressure of 220-280 mm Hg). All patients initially and 1.5 months after the EECP course had a 6-minute walk test (6MWT), an assessment of the clinical status, quality of life of patients (MLHFQ; Minnesota Living with Heart Failure Questionnaire). Computer nailfold video capillaroscopy, photoplethysmography with pulse wave recording and contour analysis, applanation tonometry to assess central aortic systolic pressure and radial augmentation index (RAI) were performed to assess the structural and functional state of large and microcirculatory vessels.Results. A statistically significant improvement in exercise tolerance (increase in distance in 6MWT from 212 [189; 273] to 308 [251; 336] m), improvement in the clinical status of patients (decrease in points on the rating scale of clinical state from 6.5±1.8 to 4.4±1,2), improvement in the quality of life according to the MLHFQ questionnaire (from 51.9±6.2 to 38.6±7.1), increase in the left ventricle ejection fraction (from 41.6 [36.6;47.1] to 44.8 [39.5;50.7]%) were found. A statistically significant improvement in endothelial function indices of both large vessels (phase shift: from 5.6 [2.4;7.2] to 6.8 [3.3;8] m/s) and microcirculatory vessels (occlusion index: from 1.5 [1.2;1.7] to 1.66 [1.3;1.9]), as well as a decrease in functional disorders of nailfold capillaries (percent of perfused capillaries, capillary network density in the reactive hyperemia test) also were found. But no statistically significant changes in the structural remodeling indices of both large and microcirculatory vessels were found.Conclusion. A positive effect of the EECP course both on the functional status with an increase in exercise tolerance and improvement in the quality of life, and on the functional state of large vessels and microvasculature was found in patients with stable CAD complicated by CHF.